The Impact of Creative Accounting Techniques on the Reliability of Financial Reporting with Particular Reference to Saudi Auditors and Academics - ismael, Ahmed Yousif Adam (International Journal of Economics and Financial Issues, 2017)
Creative accounting plays a significant role in financial reporting but it has been negatively correlated that means more managers involved in it may decrease the value of financial information, this study aims to shed light on the impact of Creative Accounting ethics techniques on the reliability of financial reporting from Auditors and Academics point of view. The data has been collected through a well-structured questionnaire is designed and will be distributed to a randomly chosen sample of certified auditors and accounting instructors in some universities. Descriptive and inferential statistics were used to generalize the results and conclude the findings. The result deduces that creative accounting techniques used by management negatively affect the reliability of financial reporting. The statutory auditor plays an important role in promoting creative accounting practice in such way that positively affect the reliability of financial reporting. Keywords: creative accounting, reliability, financial reporting. JEL Classifications: G2, M4